Knight and Moon: Dangerous Minds - Book 2 - Evanovich, Janet (New York : Bantam Books, 2017)
"The irrepressibly charming duo of Emerson Knight and Riley Moon returns in another gripping mystery by #1 New York Times bestselling author Janet Evanovich. Buddhist monk Wayan Bagus lost his island of solitude and wants to get it back. The island was about two hundred miles northeast of Samoa. It had a mountain, beaches, a rain forest, and a volcano. And now it's gone. Poof! Vanished without a trace. Brilliant and boyishly charming Emerson Knight likes nothing better than solving an unsolvable, improbable mystery. And finding a missing island is better than Christmas morning in the Knight household. When clues lead to a dark and sinister secret that is being guarded by the National Park Service, Emerson will need to assemble a crack team for help. Since a crack team isn't available, he enlists Riley Moon and his cousin Vernon. Riley Moon has a Harvard business degree and can shoot the eyes out of a grasshopper at fifty feet, but she can't figure out how to escape the vortex of Emerson Knight's odd life. Vernon has been Emerson's loyal and enthusiastic partner in crime since childhood. He now lives in an RV behind Emerson's house. Together, this ragtag, mismatched trio will embark on a worldwide investigation that will expose a conspiracy one hundred years in the making"--
"Riley Moon is a financial analyst and Emerson Knight is an eccentric billionaire's son. Together, this perfectly mismatched crime-fighting duo are looking to take down big league crime in the second mystery by #1 New York Times bestselling author Janet Evanovich"--
Library Journal Prepub Alert
Adult
Keywords: Man-woman relationships -- Fiction; Criminal investigation -- Fiction; Mystery fiction; Romantic suspense fiction